1932
DOI: 10.1113/jphysiol.1932.sp002875
|View full text |Cite
|
Sign up to set email alerts
|

The effect of lecithine on fat deposition in the liver of the normal rat

Abstract: THE very interesting effects of some component of crude lecithine upon the condition of diabetic animals have been discussed in previous communications from this laboratory [Hershey, 1930;Hershey and Soskin, 1931;Best and Hershey, 1932]. The symptoms exhibited by these animals and the autopsy findings indicate that the characteristic condition is largely attributable to failure of liver function. The results of these studies suggested that an investigation of the effect of lecithine on deposition of fat in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
4

Year Published

1935
1935
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(23 citation statements)
references
References 2 publications
1
18
0
4
Order By: Relevance
“…Links between reduced PC levels and hepatic steatosis were first recognized in rats and dogs in the 1930s (13,14) before being widely confirmed in mice and then in humans in the 1990s (15). Li et al (16) later suggested that a reduction in the PC/PE ratio affects hepatocyte membrane integrity and plays a role in the progression of steatosis to steatohepatitis in humans.…”
Section: Resultsmentioning
confidence: 99%
“…Links between reduced PC levels and hepatic steatosis were first recognized in rats and dogs in the 1930s (13,14) before being widely confirmed in mice and then in humans in the 1990s (15). Li et al (16) later suggested that a reduction in the PC/PE ratio affects hepatocyte membrane integrity and plays a role in the progression of steatosis to steatohepatitis in humans.…”
Section: Resultsmentioning
confidence: 99%
“…It is known that when rats and mice are fed a diet deficient in lipotropes (choline, methionine, folate, and vitamin B12) the liver develops steatosis within a few days (77). If the diet continues, the liver develops NASH, fibrosis, and cirrhosis, with some animals developing HCC (78).…”
Section: Mato Mouse a Novel Model That Illustrates The Importance Ofmentioning
confidence: 99%
“…The nutrient choline has three essential metabolic functions: it is a component of membrane phospholipids (1) ; it participates in lipid liver metabolism, preventing fat accumulation in the liver (2) ; and it is a precursor of acetylcholine (3) . In addition, choline prevents perosis or chondrodystrophy in poultry (4) , and it can be oxidized to betaine to donate methyl groups (5) , sharing this function with methionine, which, according to Zeisel (6) , consumes the most choline in the body.…”
Section: Introductionmentioning
confidence: 99%